A UK retrospective observational study of clinical outcomes and healthcare resource utilisation of infliximab treatment in Crohn's disease. Issue 1 (23rd May 2013) - Lindsay, J. O.; Chipperfield, R.; Giles, A.; Wheeler, C.; Orchard, T.; ,
SUMMARY Background Crohn's disease (CD) places a substantial burden on healthcare systems, with the majority of costs arising from hospitalisation and surgery. Aim To evaluate the 'real‐world' clinical effectiveness, impact on healthcare utilisation and cost of infliximab for the treatment of CD in UK practice. Methods A non‐interventional, retrospective analysis of medical records from patients with CD treated with infliximab at 18 hospital centres across the UK. The primary objective was to compare cumulative clinical outcomes and healthcare resource utilisation for the 0‐ to 24‐month post‐infliximab period with the 12 months preceding infliximab treatment. Predefined outcomes included the number of elective surgical procedures, hospitalisations and healthcare provider consultations. Costs associated with healthcare utilisation were collected from the perspective of the UK National Health Service (NHS). Results The study involved 380 patients. Infliximab significantly reduced the mean number of elective (from 0.18 to 0.11; P = 0.0035) and non‐elective (from 0.46 to 0.29; P < 0.0001) hospitalisations, and the number of consultations with gastroenterologists, gastrointestinal surgeons and radiologists (from 4.0 to 3.5, from 0.7 to 0.5 and from 0.5 to 0.2, respectively; all P < 0.001); all decreases were associated with significant cost reductions. The mean number of elective surgical procedures (including correction of severe anal fistulae and abscess drainage) was significantly reduced. Conclusions The observed reductions in numbers of hospitalisations, surgical procedures and consultations with healthcare professionals are key indicators of the clinical effectiveness of infliximab for the treatment of CD. These benefits result in overall decreases in healthcare resource utilisation, which translate into cost savings for the NHS.